Comparative transcriptomic analysis of key genes involved in flavonoid biosynthetic pathway and identification of a flavonol synthase from Artemisia annua L. (5th April 2017) - Liu, S.; Liu, L.; Tang, Y.; Xiong, S.; Long, J.; Liu, Z.; Tian, N.
Abstract: The regulatory mechanism of flavonoids, which synergise anti‐malarial and anti‐cancer compounds in Artemisia annua, is still unclear. In this study, an anthocyanidin‐accumulating mutant callus was induced from A. annua and comparative transcriptomic analysis of wild‐type and mutant calli performed, based on the next‐generation Illumina/Solexa sequencing platform and de novo assembly. A total of 82, 393 unigenes were obtained and 34, 764 unigenes were annotated in the public database. Among these, 87 unigenes were assigned to 14 structural genes involved in the flavonoid biosynthetic pathway and 37 unigenes were assigned to 17 structural genes related to metabolism of flavonoids. More than 30 unigenes were assigned to regulatory genes, including R2R3‐MYB, bHLH and WD40, which might regulate flavonoid biosynthesis. A further 29 unigenes encoding flavonoid biosynthetic enzymes or transcription factors were up‐regulated in the mutant, while 19 unigenes were down‐regulated, compared with the wild type. Expression levels of nine genes involved in the flavonoid pathway were compared using semi‐quantitative RT‐PCR, and results were consistent with comparative transcriptomic analysis. Finally, a putative flavonol synthase gene ( AaFLS1 ) was identified from enzyme assay in vitro and in vivo through heterogeneous expression, and confirmed comparative transcriptomic analysis of wild‐type and mutant callus. The present work has provided important target genes for the regulation of flavonoid biosynthesis in A. annua .